Insects as vectors for orange spotting disease in oil palm - Aliyu, Santuraki Ahmed (2017)
Virus and viroid plant diseases are responsible for enormous losses worldwide of about USD30-50 billion annually in cultivated and stored crops and are therefore major impediment to effective food production and distribution. Oil palm is one of the most important cultivated crop in Malaysia. Malaysia is one of the two major global suppliers of palm oil. Oil palm is however inflicted with many diseases, among which is an emerging disease called the orange spotting disease caused by Coconut cadang cadang viroid (CCCVd). The epidemiology of this disease is poorly understood in oil palm, including the natural transmission of CCCVd in the field. One possible mode of transmission is through insect vectors but no studies have been conducted to identify the insect vectors in any. This study was conducted to optimize extraction of CCCVd RNA from insect and to screen for possible insect vectors. Insects were collected from oil palm/coconut plantation and reared artificially in the laboratory and glass house for viroid acquisition testing. Four (4) species of insects were collected for the acquisition experiment; Oryctes rhinoceros (Beetles), Metisa plana (bagworms), Elaeidobius kamerunicus (Weevil) and Cerataphis brasiliensis (Aphids). Ten (10) oil palm seedling that has already been inoculated with CCCVd were used for feeding the selected insects vector candidates. Prior to feeding the insects, the oil palm seedlings were tested by RT-PCR, cloning and sequencing for the presence of CCCVd. RT-PCR analysis showed the presence of the expected 250 bp band in agarose gel electrophoresis indicating the presence of CCCVd RNA in the inoculated oil palm seedlings. Cloning and sequencing confirmed the presence of three CCCVd variants which had more than 98% sequence similarit with 246 nt CCCV oil palm variant. The insects were allowed to feed on the CCCVd inoculated seedlings in a cage covered with Mushin cloth. Based on their individual feeding method, the insects feed on their specific food part on infected oil palm seedlings (leaflets, inflorescence, etc.). The insects were then tested for presence of CCCVd with molecular detection using RTPCR assay with CCCVd specific primers. The total nucleic acid extracted from all four species of insects by optimised NETME and Triazol extraction. Analysis nucleic acid samples of all four insect samples using RT-PCR showed no band at the expected size of 250 bp in 1.5% agarose gel electrophoresis. To exclude error in extraction, the insect samples were extracted with plasmid CCCVd DNA using both NETME and Triazol extraction. RT-PCR analysis of plasmid mixed samples showed a band at 250 bp region but none was observed in the insect samples without the plasmid CCCVd DNA. Futhermore, four species of insects (Setora nitens, Setothosea asigna, Coptotermas curvignathus, Mahasena corbetti) collected from oil palm infected with CCCVd in the field also did not show positive bands in the RT-PCR assay. This indicates that there were no CCCVd RNA present in the tested insects and therefore, these insects might not be the vectors for CCCVd.